A conceptual framework for SPI evaluation. Issue 2 (10th October 2013) - Unterkalmsteiner, Michael; Gorschek, Tony; Islam, A. K. M. Moinul; Cheng, Chow Kian; Permadi, Rahadian Bayu; Feldt, Robert
SUMMARY Software Process Improvement (SPI) encompasses the analysis and modification of the processes within software development, aimed at improving key areas that contribute to the organizations' goals. The task of evaluating whether the selected improvement path meets these goals is challenging. On the basis of the results of a systematic literature review on SPI measurement and evaluation practices, we developed a framework (SPI Measurement and Evaluation Framework (SPI‐MEF)) that supports the planning and implementation of SPI evaluations. SPI‐MEF guides the practitioner in scoping the evaluation, determining measures, and performing the assessment. SPI‐MEF does not assume a specific approach to process improvement and can be integrated in existing measurement programs, refocusing the assessment on evaluating the improvement initiative's outcome. Sixteen industry and academic experts evaluated the framework's usability and capability to support practitioners, providing additional insights that were integrated in the application guidelines of the framework. Copyright © 2013 John Wiley & Sons, Ltd.